Demands, resources and institutional factors in the work of academic staff in Central and Eastern Europe: results of a qualitative research among university teachers in five countries - Kovács, Klára; Dobay, Beáta; Halasi, Szabolcs; Pinczés, Tamás; Tódor, Imre (Frontiers in Education, 2024)
The increased stress, pressure, and organizational change draw attention to the importance of doing research on workplace stress and resources, as well as other sources of stress among university teachers. Based on the job demands-resources theory (JD-R theory) this paper investigates the workplace factors affecting the health and well-being of Central and Eastern European (CEE) academics. A further question is, what are the institutional factors that (could) improve or worsen their well-being, as well as how they are able to cope with the stress on an individual level. For the analyses, seven focus group interviews were conducted with academics from nine higher education institutions in Hungary, Slovakia, Ukraine, Romania and Serbia (N=41). According to our results of the focus group interviews the most important workplace difficulties, challenges, and resources are related to teaching roles, interpersonal relationships, support by the management, and infrastructural conditions. Institutions can contribute to the well-being and health of the academics primarily by offering free or at least discounted participation in sports, cultural and leisure events, as well as mental health counseling, but it is important for these not to be self-serving (the colleagues from the university should not participate in the programs to make up for the missing audiences of the otherwise overfunded organizations of the institution) and haphazard: without a targeted health strategy, these are not sufficiently effective.